Empowering Agricultural Workers Through Community Health Worker-Led Pesticide Safety Workshops in Washington State - Ileana María Ponce-González; Griselda Arias; Elmer Diaz; Michael L. Parchman (SAGE Publishing, 2024)
Background It is difficult to reach migrant or refugee agricultural workers about pesticide exposure prevention. Here, we describe a community health worker (CHW)-led pesticide exposure prevention workshop and the impact of this program among migrant and refugee workers in Washington state. Methods A focus group of migrants and refugees participated in the development of a CHW-led Spanish language pesticide exposure prevention mobile phone app and workshop. Pre- and post-workshop surveys assessed pesticide training, knowledge, and characteristics. Results Community health workers facilitated 28 workshops attended by 263 participants from 49 agricultural communities. Approximately 79% of participants reported no prior pesticide training. Significant improvements were observed in the proportion familiar with illnesses associated with pesticides, knowledge about pesticide definition, ability to correctly identify the content of pesticide labels, and the correct method to wash fruits and vegetables. Conclusions Community health workers are effective in addressing the gaps in pesticide safety education and awareness among migrant and refugee communities. Further work is needed to assess how to better integrate a mobile phone app into this training and subsequent use of the knowledge.